2021
DOI: 10.1007/s10008-021-05034-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrochemical performance of LiFePO4 of cathode materials for lithium-ion batteries synthesized by surfactant-assisted solvothermal method

Abstract: Lithium iron phosphate (LiFePO 4 ) cathode materials were synthesized by the solvothermal method with the assistance of different surfactants. The influences of polyethylene glycol 2000 (PEG 2000), polyvinylpyrrolidone (PVP), and cetyltrimethyl ammonium bromide (CTAB) on the microstructure and electrochemical performance of LiFePO 4 were investigated by using X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray energy dispersive spectroscopy (EDS), electrochemical impedance spectroscopy (EIS), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Apparently, the D Li + value of LEP-12 was 1.09 × 10 –11 cm 2 s –1 , which was the highest. The results clearly indicated that the small particle size and less impurity could enhance the mobility of Li + in the olivine structure and reduce the resistance of the cathode electrolyte surface and polarization reaction, which was beneficial to enhancing the electrochemical behavior of the material …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Apparently, the D Li + value of LEP-12 was 1.09 × 10 –11 cm 2 s –1 , which was the highest. The results clearly indicated that the small particle size and less impurity could enhance the mobility of Li + in the olivine structure and reduce the resistance of the cathode electrolyte surface and polarization reaction, which was beneficial to enhancing the electrochemical behavior of the material …”
Section: Resultsmentioning
confidence: 96%
“…The results clearly indicated that the small particle size and less impurity could enhance the mobility of Li + in the olivine structure and reduce the resistance of the cathode electrolyte surface and polarization reaction, which was beneficial to enhancing the electrochemical behavior of the material. 40 Figure 7f shows the cyclic voltammetry (CV) measurement of LFP-12 in the first three cycles. It can be seen that the redox potential of the first cycle was slightly lower than those of the second and third cycles.…”
Section: Regeneration Of Lifepo 4 By LI 3 Po 4 As the Li Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…Notably, as shown in figures 6(b), (d), LFP/V/C exhibits a narrower voltage gap between the plateaus of charging and discharging compared to LFP/C, which is generally considered to be associated with better redox kinetics [30,31]. The charge/discharge curves of the LFP have become more significantly distorted and the gap widths have increased at higher current densities, indicating a more severe polarization is in the cell, which is not conducive to the long-cycle.…”
Section: Electrochemical Characterizationmentioning
confidence: 91%
“…Based on the above approach, the ratio between the reactants can be varied for Li:Fe:P = 3:1:1 along with the addition of polyethylene glycol 2000 (PEG 2000), polyvinylpyrrolidone (PVP) and cetyltrimethyl ammonium bromide (CTAB) [58]. The last three reactants act as stabilizers and growth modifiers for the morphology optimization and particle refinement of LFP.…”
Section: Hydrothermal Synthesis Of Lifepomentioning
confidence: 99%